Persepsi Pengguna Instagram Mengenai Rebranding PT PELNI (Persero): Analisis Isi Kualitatif pada Akun Resmi Instagram @pelni162 - Fahreza Khairul Yuda; Yanti Setianti Edu; Trie Damayanti Edu (Jurnal Komunikasi dan Ilmu Sosial, 2026)
This research aims to analyze social media users’ perceptions of PT PELNI’s Rebranding on social media, especially Instagram. By analyzing comments on eight posts representing changes within the company on PELNI’s official Instagram account @pelni162, this study focuses on Instagram users’ responses to PELNI’s Rebranding activities from 2023 to 2026. This research used Krippendorff’s content analysis method, with the sample units consisting of two categories of posts. The coding units are user comments that convey impressions, criticism, evaluations, support, and expectations regarding PELNI’s Rebranding activities. The contextual units refer to the time the content was posted, the context of PELNI’s Rebranding, and the position of the comment within the digital conversation in the post’s comment section. The research subject is the official Instagram account @pelni162, with the research object being comments on posts related to PELNI’s Rebranding. Data was collected through digital documentation on the official Instagram account @pelni162. The results indicate that Instagram users perceive PELNI’s Rebranding as a corporate transformation effort that demands both aesthetic visual changes and substantial changes within the company’s structure to proceed in harmony.